Effect of Thermal Processing by Spray Drying on Key Ginger Compounds - Alina Warren-Walker; Manfred Beckmann; Alison Watson; Steffan McAllister; Amanda J. Lloyd (Metabolites)
Background/Objectives: Spray drying is a technique widely employed in the food and nutraceutical industries to convert liquid extracts into stable powders, preserving their functional properties. Ginger (Zingiber officinale) is rich in bioactive compounds such as gingerols, shogaols, and zingerone, which contribute to its health benefits. This study aimed to investigate the impact of spray drying on the chemical profile of ginger, particularly focusing on the transformation of gingerols into shogaols and related compounds. Methods: Fresh ginger juice was spray-dried using various carrier agents, including Clear Gum (CO03), pea protein, and inulin. Mass spectra of the resulting powders were acquired using High-Resolution Flow Infusion Electrospray Ionisation Mass Spectrometry (HR-FIE-MS) to obtain fingerprint data. Key bioactive compounds were tentatively identified to Level 2, and their relative intensities were assessed to evaluate the effects of different carriers on the chemical composition of the ginger powders. Results: Spray drying with the commercial carrier CO03 resulted in an increase in shogaol analogues ([10]-, [8]-, and cis-[8]-shogaol), gingerenone B, and oxidation products such as 6-hydroxyshogaol, 6-dehydroshogaol, and zingerone. In contrast, natural carriers like pea protein and inulin led to lower relative intensities of these bioactives, suggesting limited capacity for promoting thermal transformations. Spray drying without a carrier produced a shogaol-dominant profile but resulted in powders with poor handling properties, such as stickiness and agglomeration. Antioxidant and total polyphenol assays showed that spray drying reduced antioxidant capacity, while total polyphenol content was more preserved; natural carriers such as inulin better maintained bioactivity compared to modified starch or pea protein. Conclusions: Among the five formulations evaluated—ginger juice with no carrier, with CO03 (two dilutions), pea protein, or inulin—CO03-based samples showed the greatest chemical transformation, while inulin and pea protein better preserved antioxidant capacity but induced fewer metabolite changes. Thus, choice of carrier in the spray-drying process influences the chemical profile and functional characteristics of resultant ginger powders. While CO03 effectively enhances the formation of bioactive shogaols and related compounds, its ultra-processed nature may not align with clean-label product trends. Natural carriers, although more label-friendly, may not create the desired chemical transformations. Therefore, optimising carrier selection is important to balance bioactivity, product stability, and consumer acceptability in the development of ginger-based functional products.